Indirect Speech Act of Spongebob Squarepants the Movie - Ima Frafika Sari (International Journal of English and Applied Linguistics (IJEAL), 2021)
Direct and indirect speech acts are the two types of speech acts. This study aims to know how indirect speech acts are employed in the movie "SpongeBob SquarePants." It employs descriptive qualitative research to explain the main character's speech act types. There is currently a scarcity of studies examining speech act types in cartoon or animation films; yet, it is necessary. According to this study, the result of this article is: first, there are seventy-four discussions of indirect speech acts obtained from all characters in the movie SpongeBob SquarePants. Each dialogue in the film SpongeBob SquarePants can be deduced to reveal the meaning of indirect speech acts. Second, The reader can use the domain analysis indirect speech acts summary to help them understand each dialogue in this movie that has a different meaning. This stage permitted the main characters to say literal things to the listener. The main character did not make a difficult-to-understand statement to the listener. This research looks at Yule's theory's utterances of indirect speech activities. As a result, the outcome differed from the prior study, despite the same issue.